PERAN YOUTH DEVELOPMENT BAGI GENERASI MILENIAL - Yoeliastuti Yoeliastuti; Faridah Faridah; Edi Wahyu Wibowo; Ria Estiana; Nurul Giswi Karomah (JURNAL ABDIMAS PLJ, 2022)
Youth is an individual who when viewed physically is experiencing development and psychologically is experiencing emotional development, so that youth are human resources for development both now and in the future. As a candidate for the next generation who will replace the previous generation. The aspect of human personality that functions to actualize its potential is called self-confidence. Problems will arise if people don't have self-confidence, and one of the weaknesses of Indonesian youth today is a lack of self-confidence. Efforts to increase self-confidence for adolescents who experience self-doubt can be done by learning and practicing. Problems that occur in students such as difficulty in adjusting, conflicts with parents or friends, personal problems, or academic problems, and unpreparedness in facing exams, then the main quality that a student must have is self-confidence. Self-confidence is one of the elements that will help individuals win life's struggles easily. Children should be told the importance of self-confidence. Pessimism and give up easily will hinder our journey. Confidence is the key to achieving goals. The problems that occur to students at PKBM 02 Karet Tengsin, Tanah Abang, Jakarta are due to the lack of self-confidence of students. The series of implementation of service activities are carried out in two stages. The first stage is observation where the university visits PKBM Research and Technology 02 Karet Tengsin, Tanah Abang to identify problems that occur in students regarding self-development problems. The second stage is to carry out activities to provide material on increasing self-development for the millennial generation.Keyword: self development, millennial generation